Bioelectrochemical single-walled carbon nanotubes. - Azamian, B; Davis, J; Coleman, K; Bagshaw, C; Green, M (2002)
Metalloproteins and enzymes can be immobilized on SWNTs of different surface chemistry. The combination of high surface area, robust immobilization and inherent nanotube electrochemical properties is of promising application in bioelectrochemistry.